#TITLE_ALTERNATIVE# - SOFWAN (NIM : 24212003), MUHAMMAD
Terminal is a public service facility unit, in this case for the movements of people and freights from one point to another. As a public facility, a terminal should be capable of providing services to communities as good as possible. In realizing an effective, efficient transportation system in Pekanbaru City, a representative, lavish, wide Inter-City, Inter-Province (AKAP) passenger terminal has been built, Bandar Raya Payung Sekaki (BRPS) terminal. Since being operated in 2006, the terminal has not operated optimally yet. Most public transportation buses have been reluctant to enter into it to take and to drop passengers, though Pekanbaru City Transportation Agency has imposed disciplinary action. Thus, at some locations in Pekanbaru City emerged shadow terminals, resulting in jamming at some roads. Based on the problem formulation above, the objective of study was to evaluate the performance of BRPS terminal’s function and to formulate the measures of optimizing its function. Related to the objective above, some stages were conducted, namely, evaluating BRPS terminal on a basis of the perceptions of public transportation passengers and on the perceptions of Public Transportation Carriers (PAU) by using an Analytical Hierarchy Process (AHP) method, where the criteria applied were safety, security, cleanness and healthy, convenience, and location factors. Next, the further stage formulated the policies of optimizing BRPS terminal’s functions based on the results of evaluation carried out in earlier stages. Based on the result of analysis, the elements of criteria found from an AHP analysis was obtained in form of location factor from both aspects of passengers’ perceptions and public transportation carriers’. The sub-criterion with the highest eigen value was public transportation frequency factor (0.233) based on public passengers’ perception, whereas based on the PAU’s perceptions the sub-criterion with the highest eigen value was terminal cost factor (0.387). By the result of evaluating BRPS terminal obtained, the measures of optimizing BRPS terminal’s function were formulated with some priorities feasible from both passenger and PAU sides. From the passenger side, the measures were improving the quality of Pekanbaru Trans Metro bus services in both frequency and routes that serve the terminal. Meanwhile, from PAU side, the measures were offering some benefits to the carriers in form of transportation operational cost by reducing the terminal retribution fee to pay by the carriers. With the analytical results obtained previously, some recommendation were formulated useful for the policy makers, in this case Pekanbaru City government: first priority is to improve the performance of Bandar Raya Payung Sekaki passenger terminal supporting system, particularly Trans Metro Pekanbaru, especially from the aspects of frequency of Trans Metro Pekanbaru bus services and the number of routes that serve the BRPS terminal. Second priority is to offer some benefits to the carriers in form of transportation operational cost by reducing the terminal retribution fee to pay by the carriers. And the third priority is to repair and enhance the quality of road in Pekanbaru, particularly main roads toward Bandar Raya Payung Sekaki terminal to make it easier for passengers and public transports toward Bandar Raya Payung Sekaki terminal.